Kobiety u Tertuliana w kontekście historii zbawienia - Zalewski, Dariusz (Vox Patrum, 2018)
The analysis of the writings of Tertullian at an angle of his attitude towards women encounters a lot of difficulties. On one side when addressing to women he uses rather waspish, incisive language sometimes even with a rhetorical emphasis. We can see it at some instructive, moral fragments of the letters such as De cultu feminarum or De virginibus velandis. Superficial reading of these versets could lead up to a conclusion about antifeminism of Tertullian. On the other side he highly appreciates women because of their participation by body and sole at the God’s redemption and universal resurrection. It is clearly seen at some of his theological works such as, for example, De resurrectione mortuorum. Tertullian is not a writer who habitually looks for and show every negative characteristic feature of woman’s character. All his manifestations of distrust towards women derive rather from his own character and prepossession to moral rigorism and partially reflect psyche of people constituting Christian communities at II and III centuries after Christ. At the same time we could say that the apparent discrepancy of his point of view towards women results not only from gradual changing of his attitude to women but mainly from the character of his works and aims he wanted to achieve.